The Concept of Value: A Rejoinder - Clark, J. M. (Quarterly Journal of Economics, 1915)
I. Points of agreement, 709. — Need of economic standards independent of price, 710. — The place of inappropriables, 711. — Weighting of individuals in social value, 712. — Conflicts of values, 713. — Values of institutions should be imputed to institutions, not to single commodities, 715. — Marginal method reversed, 715. — Some of the requirements of a social theory of value, 716. — II. Dual nature of Professor Anderson's concept, 716. — Term "rate" avoids a confusion, 717. — III. Doctrine v. definition, 718. — Doctrine criticized by Professor Anderson not implied in the mere definition of value, 719. — Examples, 720. — IV. Use of the relative concept, 720. — "Assuming a fixed value of money, " and other criticisms, 721. — V. Economic v. non-economic, 722. — Values of institutions not to be taken for granted as something supreme and apart from single exchanges, 723. — Conclusion, 723.